Predicting process-induced distortion for composite structures - Yan, Shuang (2024)
Process-induced distortion (PID) is inevitable during the manufacturing of composite structures. A precise prediction of PID would benefit the design and manufacturing process so that the dimensional accuracy of the produced composite part is within tolerance. In this work, a sequentially coupled thermal-chemical and mechanical model was developed to predict the chemical, thermal and tool-part interaction (TPI) effects contributing to PID. The proposed model was based on the Cure Hardening Instantaneous Linear Elastic (CHILE) constitutive law and executed within ABAQUS finite element analysis, with the mechanical and thermal material properties defined through user subroutines.